Shaping current European mitochondrial haplogroup frequency in response to infection: the case of SARS-CoV-2 severity - José Luis Cabrera-Alarcon; Raquel Cruz; Marina Rosa-Moreno; Ana Latorre-Pellicer; Silvia Diz de Almeida; Scourge Cohort Group; José A. Riancho; Augusto Rojas-Martinez; Carlos Flores; Pablo Lapunzina; Fátima Sánchez-Cabo; Ángel Carracedo; et al. (Communications Biology)
Abstract The frequency of mitochondrial DNA haplogroups (mtDNA-HG) in humans is known to be shaped by migration and repopulation. Mounting evidence indicates that mtDNA-HG are not phenotypically neutral, and selection may contribute to its distribution. Haplogroup H, the most abundant in Europe, improved survival in sepsis. Here we developed a random forest trained model for mitochondrial haplogroup calling using data procured from GWAS arrays. Our results reveal that in the context of the SARS-CoV-2 pandemic, HV branch were found to represent protective factors against the development of critical SARS-CoV-2 in an analysis of 14,349 patients. These results highlight the role of mtDNA in the response to infectious diseases and support the proposal that its expansion and population proportion has been influenced by selection through successive pandemics.